Faktor-Faktor yang Mempengaruhi Penemuan Penderita TB Paru di Kota Palu Provinsi Sulawesi Tengah - Awusi RYE, Yusrizal Djam’an Saleh2, Yuwono Hadiwijoyo (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Every second Mycobacterium tuberculosis infected 1 person worldwide. Overall, one-third of the world’s population is currently infected with the TB bacillus. 5%-10% of people who are infected with TB bacilli become sick or infectious at some time during their life. Pulmonary TB is an important health problem in worldwide. World Health Organization (WHO) recommended controlling TB with DOTS strategy since 1995. Focus of global TB control with DOTS strategy is case detection and cure TB patients. Case detection rate in South East Asia is low (31%-54%) of the target global of CDR (70%). For the period 2006-2007 years CDR in Palu Municipalyti is very low (34%-35%). Therefore, it is important to find factors that influence for case detection of pulmonary TB.Objectives: To identify the relationship between independent variables of knowledge, length of work, work load, incentive, training of DOTS, access, service KIE about TB and screening suspect TB with case detection of pulmonary TBMaterial and Methods: This was an analytic observational study which used a cross sectional design with both quantitative and qualitative approaches. Subjects of the study were providers TB program of Community Health Center in Palu Municipality. Data were descriptively analyzed (univariate) and statistically analyzed (bivariate) using chi square test and logistic regression (multivariate) at confident interval 95%.and significant level 5%.Results: Variables that have significant statistically relationship (p< 0.05) with case detection of pulmonary TB is screening suspect TB (OR=8,92; 95%CI=2,36-38,65), service KIE about TB (OR=8,85; 95%CI=2,16-36,97), training of DOTS (OR=5,84; 95%CI=1,54-26,77).Conclusion: The factors to have significant influence of case detection pulmonary TB were screening suspect TB, service CIE TB and training of DOTS. Screening suspect TB was the most influencing case detection of pulmonary TB in Palu Municipality.Keywords: case detection of Pulmonary TB, screening of TB suspect, service CIE, training of DOTS, Palu municipality